Pyrolytic Behavior of Long-Chain Alkyl Quaternary Ammonium Bromide Inside Nanopores - Niu, Yanhui; Yu, Wenbin; Yang, Shuguang; Wan, Quan (Frontiers in Energy Research, 2021)
The pyrolytic behavior of organic matter inside nanopores was studied by simultaneous thermogravimetric/differential scanning calorimetry analyzer coupled with Fourier transform infrared spectroscopy (TG/STA-FTIR). Nanoporous silica was prepared through a hydrothermal method using long-chain alkyl quaternary ammonium bromide (CnTAB, n=12,14) as a template. The pyrolytic behavior of CnTAB inside nanopores with different diameters was studied and that of CnTAB inside and outside nanopores was compared. The results showed that the pyrolytic removal process of CnTAB underwent carbon chain decomposition and oxidation, the DSC exothermal peak of CnTAB comes mainly from oxidative combustion, the oxidative combustion temperature decreases with the increase of pore size, the CnTAB inside nanopores occurred crystallization-amorphous state phase transition, the calcined nanopore can again inhale CnTAB into the nanopore, and the pyrolytic behavior of CnTAB inside the calcined nanopores is similar to that of the uncalcined nanopores. This work aims to understand the storage and transformation processes of organic hydrocarbons under nanopore-confinement effect.